Call for Papers Materiali di Estetica 12. 1 : “Music and Empathy: New Research Perspectives” (Materiali di Estetica. Terza serie, 2024)
Call for PapersMateriali di Estetica 12. 1 – “Music and Empathy: New Research Perspectives”
Keywords: Call for Papers; materiali di estetica; music; music and empathy